MIKOALGA SPIRULINA PLATENSIS SEBAGAI SUPLEMEN UNTUK MENINGKATKAN GIZI DAN IMUNITAS BALITA DI POSYANDU ANGGREK 2 KELURAHAN SEBERANG PADANG, KOTA PADANG - Armaini Armaini; Yetria Rilda; Netti Suharti (Jurnal Hilirisasi IPTEKS, 2020)
Patients with malnutrition mostly were golden age toddlers under 2 years. Based on the survey conducted, it was found toddler of the Posyandu Anggrek 2 experienced malnutrition. The community partnership program provides solutions to improve nutrition, especially for toddlers by utilizing the nutrient-rich Spirullina platensis microalgae as a nutritional supplement in the toddler's diet. The main objective of the community partnership program implemented at Posyandu Anggrek 2 is to provide Spirullina platensis capsule supplements to improve nutrition in under-fives with malnutrition and malnutrition, to increase knowledge of mothers of toddlers about highly nutritious foods, especially Spirullina platensis microalgae to improve nutrition, immunity and health toddlers during the current Covid-19 epidemic. The application of Spirullina platensis cultivation technology which is transferred to housewives who are members of Posyandu Anggrek 2. The success of this program shows that giving Spirullina platensis capsules to 10 toddlers for 6 weeks can increase toddler nutrition as measured based on the WHO standard Anthropometric index. The increase in body weight and height after administration of Spirullina platensis was seen in all toddler, and there was an increase in health and immunity in toddler. It can be concluded that giving Spirullina platensis capsules is beneficial for improving nutritional status and immunity in toddlers.